Synthesis of Effective Kinetic Inhibitors for Natural Gas Hydrates - Lou, Xia; Ding, Ailin; Maeda, N.; Wang, Shuo; Kozielski, K.; Hartley, P. (American Chemical Society, 2012)
Six novel polymer-based kinetic hydrate inhibitors (KHIs) were synthesized and characterized. Their performance in inhibiting both tetrahydrofuran (THF) hydrate and the synthetic gas hydrate formation was examined using two different instruments: a ball-stop apparatus and a high-pressure automatic lag time apparatus (HP-ALTA). Performance was benchmarked against two commercially available KHIs, Gaffix VC-713 and Luvicap EG, under the same working conditions. The test results from the ball-stop rig demonstrated that the new KHIs were as effective as Gaffix VC-713 and Luvicap EG in preventing the formation of THF hydrates in 3.5 wt % NaCl solutions. For the synthetic gases, most new polymers outperformed the reference KHIs at a concentration of 0.05 wt %. Polymers containing a pendant THF functional group in the side chains showed a substantial 12-16 °C decrease in the hydrate formation temperature of the gas water mixtures relative to those containing the same amount of Gaffix VC-713 or Luvicap EG. The trend of the inhibition performance of the polymers was different in THF from that measured for gas mixtures. Small amounts of ethanol added to the hydrate formation mixtures were also shown to have an effect. Investigation of the inhibition mechanism associated with these new polymers is under way.